Comparison between British Comparative Thromboplastin (BCT) and a Factor II-VII-X Determination Method (Simplastin A) Based on Fresh Plasma Samples from Dicoumarol-Treated Patients - Korsan-Bengtsen, K; Johsen, M; Pehrsson, N.-G (Thrombosis and Haemostasis, 1977)
Comparisons between British Comparative Thromboplastin (BCT) and a factor II-VII-X determination method – Simplastin A – have been carried out monthly during the time from December 1973 to March 1976. On each occasion fresh plasma from 20 dicoumarol-treated patients was analyzed with the two methods. It was found that the linear regression model is well suited for the comparison, that the BCT thromboplastin did not change significantly during the study, and that the method of comparing has a coefficient of variation of approximately 6–8 %. This means, for instance, that a ratio of 3.8 with BCT corresponds to a ratio of 3.5 ± 0.26 with Simplastin A. Thus in one period you may have ratio 3 and in another ratio 4 as the lower limit of the therapeutic range although you use the same thromboplastin and the same method. The importance of having a stable reference thromboplastin and an established method of comparing thromboplastins is stressed.